Digital Economy : Economic Innovation Through Digital Branding Via Instagram Platform for MSMEs - Rozzaqi, Muhammad Syahrul (IDFoS Indonesia, 2022)
This research aimed to describe how Fadil Jaidi’s endorsement content on Instagram, to analyse Fadil Jaidi’s personal branding on Instagram in relation to endorsement content, and to determine the impact of Fadil Jaidi’s endorsements. This was qualitative research. The results of the research showed that Fadil Jaidi’s endorsement content could influence the audience and also his MSMEs. This was an innovative result that also represented the economic environment transitioning from direct shopping to online shopping, with Fadil Jaidi himself being one of the Gen Z influencers who significantly impacted consumer purchasing power and sales for MSME owners, who were also predominantly Gen Z. Additionally, Fadil Jaidi’s engaging endorsement content had turned Instagram into a new environment where advertising or marketing no longer needs to be done manually, especially in the pandemic era where people had limitations in accessibility, and even post-pandemic where society had become accustomed to using and accessing everything through digital media, making digital media a more frequently encountered social environment due to its unlimited space and time.